Simple and Rapid Method for Determination of Abemaciclib in Human Serum using Supported Liquid Extraction Pretreatment and LC-MS/MS Analysis - Naoto Sekizaki; Hideaki Yashima; Takuya Araki; Koujirou Yamamoto (Indonesian Journal of Pharmaceutics, 2020)
We developed a simple and rapid method for the determination of abemaciclib in human serum using supported liquid extraction (SLE) method for pretreatment and LC-MS/MS. Abemaciclib was extracted using SLE method with methyltert-butyl ether (MTBE) as elution buffer, and analyzed by LC-QTOF MS system, LCMS9030 (Shimadzu). Abemaciclib and fluconazole (internal standard) were detected with ESI spray in positive ionization mode, and the transition were set at 507.3/393.1629 for abemaciclib and 307.1/220.0677 for fluconazole. The retention times of abemaciclib and fluconazole were 2.76 and 2.98 min, respectively, and good linearity was obtained from 20–1,000 ng/mL for abemaciclib. The regression equation (weight = 1/x2) describing the calibration curve in human serum was y = 0.0196 x – 0.056 (R2 = 0.999), where y is the peak area ratio of abemaciclib against the IS and x is the nominal concentration of abemaciclib. The intra- and inter-assay accuracy varied between -4.3–1.7%, and the precision varied between 0.90–6.19%. The mean recovery rate of abemaciclib was 87.7 ± 4.3%, and the mean matrix factor was 1.00 ± 0.083. Our method offers speed and simplicity of sample preparation, which is one of great advantages in the analysis of clinical specimens. We believe that the present method will contribute to establishing a methodology for determining the optimal dose of abemaciclib for individual patients. Key words: abemaciclib, SLE, supported liquid extraction, quantification